Bacillus thuringiensis in caterpillars and associated materials collected from protected tropical forests in northwestern Costa Rica - Rodríguez-Sánchez, César; Sittenfeld, Ana; H. Janzen, Daniel; Espinoza, Ana M. (Revista de Biología Tropical, 2006)
Bacillus thuringiensis (Bt) synthesizes crystalline inclusions that are toxic to caterpillars (Lepidoptera) and other orders of invertebrates. Materials associated with 37 caterpillars from 16 species, collected while feed-ing on 15 different species of host plants in dry, cloud and rain forests located in the Área de Conservación Guanacaste in northwestern Costa Rica, were examined for the presence of Bt. From a total of 101 derived samples, 25 Bt isolates were cultured: 56% from host plant leaves, 8% from caterpillar guts and 36% from cater-pillar fecal pellets. Bt was isolated from at least one sample in 38% of the systems constituted by the food plant, gut and fecal pellets corresponding to a single caterpillar. Four different morphologies of crystalline inclusions were observed, with bipyramidal and irregular crystal morphologies being the most prevalent.